Communicating risk during early phases of COVID-19: Comparing governing structures for emergency risk communication across four contexts - Geurts, Brogan; Weishaar, Heide; Mari Saez, Almudena; Cristea, Florin; Rocha, Carlos; Aminu, Kafayat; Tan, Melisa Mei Jin; Salim Camara, Bienvenu; Barry, Lansana; Thea, Paul; Boucsein, Johannes; Bahr, Thurid; et al. (Frontiers in Public Health, 2023)
Background: Emergency risk communication (ERC) is key to achieving compliance with public health measures during pandemics. Yet, the factors that facilitated ERC during COVID-19 have not been analysed. We compare ERC in the early stages of the pandemic across four socio-economic settings to identify how risk communication can be improved in public health emergencies (PHE). Methods: To map and assess the content, process, actors and context of ERC in Germany, Guinea, Nigeria and Singapore, we performed a qualitative document review, and thematically analysed semi-structured key informant interviews with 155 stakeholders involved in ERC at national and sub-national levels. We applied Walt and Gilson’s health policy triangle as a framework to structure the results. Results: We identified distinct ERC strategies in each of the four countries. Various actors, including governmental leads, experts, and organisations with close contact to the public, collaborated closely to implement ERC strategies. Early integration of ERC into preparedness and response plans, lessons from previous experiences, existing structures and networks, and clear leadership were identified as crucial for ensuring message clarity, consistency, relevance, and an efficient use of resources. Areas of improvement primarily included two-way communication, community engagement, and monitoring and evaluation. Countries with recurrent experiences of pandemics appeared to be more prepared and equipped to implement ERC strategies. Conclusion: We found that considerable potential exists for countries to improve communication during public health emergencies, particularly in the areas of bilateral communication and community engagement as well as monitoring and evaluation. Building adaptive structures and maintaining long-term relationships with at-risk communities reportedly facilitated suitable communication. The findings suggest considerable potential and transferable learning opportunities exist between countries in the global north and countries in the global south with experience of managing outbreaks.